2021
DOI: 10.1111/jfd.13341
|View full text |Cite
|
Sign up to set email alerts
|

Genetic homogeneity coupled with morphometric variability suggests high phenotypic plasticity in the sea louse Caligus rogercresseyi (Boxshall and Bravo, 2000), infecting farmed salmon (Salmo salar) along a wide latitudinal range in southern Chile

Abstract: The sea louse Caligus rogercresseyi is the most important pathogen causing “caligidosis” in the Chilean salmon industry. In this study, using cox1 gene, we evaluate the genetic variation of C. rogercresseyi from farmed Salmo salar along a latitudinal range (40°–52°S) in south Chile to determine whether morphological differences are explained by genetic or environmental factors. Female parasites were randomly collected from S. salar at five farms. Body variation was examined using multivariate analyses and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Bravo et al 42 reported that at low temperature the adult lice are longer than at higher temperature. The same observations were made by Gonzalez et al 54 who reported that C. rogercresseyi exhibited significant morphometric variability among sites and that the lice collected from southern regions (>54 LS) were longer than lice collected in Region X (42 LS). Larger lice have been also reported during colder temperature for L. salmonis.…”
Section: Temperaturesupporting
confidence: 82%
See 1 more Smart Citation
“…Bravo et al 42 reported that at low temperature the adult lice are longer than at higher temperature. The same observations were made by Gonzalez et al 54 who reported that C. rogercresseyi exhibited significant morphometric variability among sites and that the lice collected from southern regions (>54 LS) were longer than lice collected in Region X (42 LS). Larger lice have been also reported during colder temperature for L. salmonis.…”
Section: Temperaturesupporting
confidence: 82%
“…The same situation could have occurred with C. rogercresseyi in southern Chile, as resistance has developed against most of the medicines used for its control. The lice have shown a big plasticity and adaption to adverse environmental conditions 25,54 …”
Section: Factors Affecting the Abundance Of C Rogercresseyimentioning
confidence: 99%
“…Cytochrome oxidase subunit I gene (COI) sequences are one of the most reliable among multiple other DNA barcodes to investigate genetic variation with phenotypic plasticity since it is a genetic marker with a high genetic variation 51 . Various studies combining COI variation and phenotypic plasticity were conducted throughout different invertebrates' phyla including tardigrades 9,21,52,53,54,55 , proving the markers accuracy in this groups of organisms. In the result, high genetic homogeneity has been observed for organisms with wide geographical distribution altogether with well visible morphological differences i.e., phenotypic plasticity 53 .…”
Section: Genetic Comparison Of Different Populations Of the Pam Fairb...mentioning
confidence: 96%
“…Various studies combining COI variation and phenotypic plasticity were conducted throughout different invertebrates' phyla including tardigrades 9,21,52,53,54,55 , proving the markers accuracy in this groups of organisms. In the result, high genetic homogeneity has been observed for organisms with wide geographical distribution altogether with well visible morphological differences i.e., phenotypic plasticity 53 .…”
Section: Genetic Comparison Of Different Populations Of the Pam Fairb...mentioning
confidence: 96%
“…Space–time patterns suppose parasitic aggregation across the geographic area occupied by salmon farming, with an increase in risk around predetermined sites. Also, the genetic analysis of C. rogercresseyi along a latitudinal range (40°-52°S) in southern Chile proposes genetic homogeneity, morphometric variability among sites, and longest parasites from >52°S ( 20 ). However, location areas associated with different infestation levels of C. rogercresseyi throughout three regions of Chile had not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%